THE ROLE OF PARENTAL ACADEMIC SOCIALIZATION AND FRIENDSHIP QUALITY IN ENHANCING SCHOOL CONTINUATION MOTIVATION AMONG RURAL ADOLESCENTS - Aprilia, Nurazizah; Alfiasari, Alfiasari (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2025)
Educational motivation is a pivotal predictor of long-term academic success, particularly for adolescents in rural communities characterized by limited educational resources, socioeconomic vulnerability, and reduced access to structured academic support. This study aims to empirically examine the influence of parental academic socialization and friendship quality on rural adolescents’ motivation to continue schooling, while also controlling for individual and family background characteristics. Utilizing a quantitative explanatory design, data were collected from 116 ninth-grade students in Cijeruk District, Bogor Regency, Indonesia. Descriptive analyses indicate that levels of parental academic socialization and peer relationship quality were generally low, with school motivation rated at a moderate level. Multiple regression analyses revealed that both parental academic engagement and high-quality friendships significantly and positively predicted educational motivation. This research contributes to the growing literature on educational resilience by evidencing the simultaneous role of familial and peer-based social capital in fostering persistence in education. The study offers contextually relevant implications for rural education policy, highlighting the need for integrative interventions that empower families and facilitate prosocial peer dynamics. Its novelty lies in bridging two critical but often separately examined dimensions of social support within an underrepresented spatial context in global educational research.